The Roles Of Village Apparatus In Implementing Qanun Number 3 Of 2017 In Jangka Alue, Sub-District Of Jangka, Bireuen, Aceh Province - Dian Eriani; Ade Soraya (Universitas of Muhammadiyah Makassar, 2023)
The implementation of Qanun Gampong Number 3 of 2017 concerning Smoke and drugs-Free Homes is an example of a healthy and prosperous village. This study describes the role of the village apparatus and their influence on the community. The method used in this research is descriptive, socio-legal research approach with the theory of authority. The types of secondary and primary data sources were then analyzed using qualitative techniques. The study was conducted in the village of Jangka Alue, Jangka District, Bireuen Regency, Aceh. Base on the result of the research, the role of the village apparatus are to encourage and prohibit, to establishment an anti-smoking and drug task force, to form a qanun on ureung chiek geutanyo, to give appreciation and supervision that carried out in accordance with the authority to contribute in the administration of government, community development, community empowerment and community development in accordance with orders. Constitution. Impact on society, creating a sense of security, reducing smoking. Community health and welfare have not been felt because there are no indicators as benchmarks.